Bio-hythane production from microalgae biomass: Key challenges and potential opportunities for algal bio-refineries. (October 2017) - Ghimire, Anish; Kumar, Gopalakrishnan; Sivagurunathan, Periyasamy; Shobana, Sutha; Saratale, Ganesh D.; Kim, Hyun Woo; Luongo, Vincenzo; Esposito, Giovanni; Munoz, Raul
Highlights: This review focused on the generation of bio-hythane (H2  + CH4 ) from microalgae. Key issues affecting H2  + CH4 production via two-stage fermentation is presented. Discussed various strategies for enhancing biohythane production. Several crucial factors for technology scale up for H2  + CH4 have been highlighted. Abstract: The interest in microalgae for wastewater treatment and liquid bio-fuels production (i.e. biodiesel and bioethanol) is steadily increasing due to the energy demand of the ultra-modern technological world. The associated biomass and by-product residues generated from these processes can be utilized as a feedstock in anaerobic fermentation for the production of gaseous bio-fuels. In this context, dark fermentation coupled with anaerobic digestion can be a potential technology for the production of hydrogen and methane from these residual algal biomasses. The mixture of these gaseous bio-fuels, known as hythane, has superior characteristics and is increasingly regarded as an alternative to fossil fuels. This review provides the current developments achieved in the conversion of algal biomass to bio-hythane (H2  + CH4 ).